Probiotics Addition Potential to Increase Body Weight, Feed Consumption and Feed Conversion on Pre-Layer Laying Hens - Sukmawati Lailatul Jannah; Mirni Lamid; Mohammad Sukmanadi; Mohammad Anam Al Arif; Sri Hidanah; Sri Chusniati (Jurnal Agro Veteriner, 2023)
Probiotics are all forms of microbial cell preparations or components of microbial cells that have a beneficial effect on the health and life of the host. Some feed additives such as the Antibiotic Growth Promoter (AGP) hormone have been banned. Therefore, nowadays, probiotics are often used as additives to replace antibiotics. The probiotics that are widely used are lactic acid bacteria because they can increase the efficiency of digestion and absorption of nutrients. The purpose of this study was to determine the effect of giving probiotics a combination of Bacillus coagulans and Bacillus subtilis with doses of 2 ml, 4 ml, and 6 ml/head/day orally on weight gain, feed consumption, and decreased feed conversion of laying hens. This study was conducted for 2 weeks using pre layer chickens aged 21 weeks to 23 weeks old as many as 24 chickens, randomized into 4 treatments with 6 replications with P0 as control, P1 = 2 ml, P2 = 4 ml, and P3 = 6 ml. The probiotic used is a combination of probiotics Bacillus coagulans and Bacillus subtilis with a concentration of 1x107 CFU/ml in liquid.